Track Performance in Tunnels and Rail Transition Areas with Under Tie Pads and Under Ballast Mats - Riding, Kyle A.; Bridge, Jennifer A.; Davis, Justin R.; Guan, Shanyue; Gonzalez, Stephen (Rural Railroad Safety Center, Kansas State University., 2022)
Railroads have begun to use under tie pads (UTP) and under ballast mats (UBM) in rail track construction to reduce maintenance costs by better distributing loads, reducing the track modulus, and increasing ballast contact areas with ties. Locations such as tunnels, bridges, and bridge approaches are especially strong candidates for UTP and UBM use due to the high support stiffness they provide to the ballast. In this study, the University of Florida (UF) instrumented the Virginia Avenue Tunnel in Washington D.C., which uses UTP and UBM, during construction to monitor track pressure distribution, tie movement, and tunnel floor vibration during the first 20 months of use (July 2018 – February 2020). Track pressure distributions across ties were measured for hundreds of trains at the tunnel floor transition area and inside the tunnel. Measurements showed that the track settlement occurred over the first 6 months of measurement after track was opened, after which it stabilized to less than 0.157 in. (4 mm).